Neural spatio-temporal patterns of information processing related to cognitive conflict and correct or false recognitions - Romuald A. Janik; Igor T. Podolak; Łukasz Struski; Anna Ceglarek; Koryna Lewandowska; Barbara Sikora-Wachowicz; Tadeusz Marek; Magdalena Fafrowicz (Scientific Reports, 2022)
Abstract Using a visual short-term memory task and employing a new methodological approach, we analyzed neural responses from the perspective of the conflict level and correctness/erroneous over a longer time window. Sixty-five participants performed the short-term memory task in the fMRI scanner. We explore neural spatio-temporal patterns of information processing in the context of correct or erroneous response and high or low level of cognitive conflict using classical fMRI analysis, surface-based cortical data, temporal analysis of interpolated mean activations, and machine learning classifiers. Our results provide evidence that information processing dynamics during the retrieval process vary depending on the correct or false recognition—for stimuli inducing a high level of cognitive conflict and erroneous response, information processing is prolonged. The observed phenomenon may be interpreted as the manifestation of the brain’s preparation for future goal-directed action.